Analyzing the implementation of collaborative governance to accelerate the stunting reduction program in South Tangerang City - Ilham Pambudi; Vishnu Juwono (Universitas Teuku Umar, 2026)
This study aims to analyze the implementation of collaborative governance and identify key factors influencing its effectiveness in accelerating the stunting reduction program in South Tangerang City. Using a post-positivist approach, this research combines theoretical perspectives on collaborative governance with empirical field observations. Data were collected through in-depth interviews, document analysis, and observation involving government agencies, health institutions, and related stakeholders engaged in stunting prevention initiatives. The findings indicate that South Tangerang City has initiated collaborative efforts across sectors; however, the collaboration has not yet operated optimally due to weak institutional design, unclear coordination mechanisms, and limited facilitative leadership. These shortcomings hinder stakeholder engagement, shared decision-making, and sustained commitment in program implementation. The study concludes that strengthening institutional arrangements, enhancing facilitative leadership, and improving stakeholder integration are essential to optimizing collaborative governance in stunting reduction programs. By addressing these critical factors, local governments can improve policy coherence, program effectiveness, and collective action in tackling stunting. This research contributes to the development of collaborative governance practices and provides a conceptual and practical reference for municipal administrations seeking to accelerate stunting reduction through effective multi-stakeholder collaboration.